Mass transport and changes in the saccharide profile during osmotic dehydration of apricot and chokeberry fruits - Pluta, Małgorzata; Klewicki, Robert (Wydawnictwo Politechniki Łódzkiej, 2022)
The aim of the study was to determine the effect of osmotic dehydration in sucrose solution on the level and profile of the main saccharides in frozen chokeberry and apricot. A 50°Bx sucrose solution at a temperature of 25, 35, 45 and 55°C was used in the tests. The influence of temperature and dehydration time on the dry matter content in the tested fruits was demonstrated. Both in apricot and chokeberry the highest increase was recorded in the first hour of the process, for apricots to the level of 25.1-32.4%, for chokeberry 30.4-33.4%. The use of the highest temperature (55°C) increased the content of glucose and fructose while reducing the amount of sucrose (hydrolysis); at 25-35°C the opposite effect was obtained. At low temperatures, chokeberry was not very susceptible to migration of sucrose. Also, the transport of water was not intense. There was no correlation between the temperature of the process and the increase in dry matter in the sample. The greatest loss of water, i.e. 1 g H2O/g i.d.m., occurred after five hours at 55°C. Under analogous conditions, apricots showed a higher water loss, at the level of 4.68 g H2O/g i.d.m. At 25°C, after the first hour of dehydration, the energy value of saccharides in apricots was 315 kJ/100 g; at 55°C, after 3÷5 hours it fluctuated around 500 kJ/100g. Dehydrated chokeberry was characterized by approx. 1.5÷2 times lower energy value than apricot.
Keywords: osmotic dehydration; saccharides profile; apricot; chokeberry; odwodnienie osmotyczne; profil sacharydów; morela; aronia